Inhibition of Anti-Inflammatory Macrophage Phenotype Reduces Tumour Growth in Mouse Models of Brain Metastasis - Economopoulos, Vasiliki; Pannell, Maria; Johanssen, Vanessa A.; Scott, Helen; Andreou, Kleopatra E.; Larkin, James R.; Sibson, Nicola R. (Frontiers in Oncology, 2022)
Breast cancer brain metastasis is a significant clinical problem and carries a poor prognosis. Although it is well-established that macrophages are a primary component of the brain metastasis microenvironment, the role of blood-derived macrophages (BDM) and brain-resident microglia in the progression of brain metastases remains uncertain. The aim of this study, therefore, was to determine the role, specifically, of pro- and anti-inflammatory BDM and microglial phenotypes on metastasis progression. Initial in vitro studies demonstrated decreased migration of EO771 metastatic breast cancer cells in the presence of pro-inflammatory, but not anti-inflammatory, stimulated RAW 264.7 macrophages. In vivo, suppression of the anti-inflammatory BDM phenotype, specifically, via myeloid knock out of Krüppel-like Factor 4 (KLF4) significantly reduced EO771 tumour growth in the brains of C57BL/6 mice. Further, pharmacological inhibition of the anti-inflammatory BDM and/or microglial phenotypes, via either Colony Stimulating Factor 1 Receptor (CSF-1R) or STAT6 pathways, significantly decreased tumour burden in two different syngeneic mouse models of breast cancer brain metastasis. These findings suggest that switching BDM and microglia towards a more pro-inflammatory phenotype may be an effective therapeutic strategy in brain metastasis.